P67 Switch to other nucleos(t)ide analogues therapy in chronic hepatitis B cohort on long-term de-novo combination therapy with lamivudine plus adefovir: efficacy and safety. (6th September 2011) - Carey, I; Mendes, A; Joshi, D; Bruce, M; Knighton, S; Scalori, A; Hughes, S; Al-Freah, M; Suddle, A; Harrison, P M; Agarwal, K
Abstract : Introduction: Long-term de-novo combination therapy with lamivudine (LAM) 100 mg/d + adefovir (ADV) 10 mg/d is highly efficient, with no/minimal drug resistance and good safety profile. Tenofovir (TDF) 245 mg/d or entecavir (ETV) 0.5 mg/d are highly efficacious antivirals with high resistance barrier and provide alternative to LAM + ADV combination therapy. Aim: We aimed to investigate the virological and serological responses and renal/bone safety after switch from LAM + ADV to other antiviral drugs. Method: Patients: Nucleos(t)ide analogues naive 192 CHB patients (78% males, median age 40 y, 35% HBeAg+, 34% cirrhosis) were treated with de-novo LAM+ADV at a single-centre practice (median 36 months). 149 patients from this cohort were switched to other nucleos(t)ide analogues therapy: 101 (68%) to TDF monotherapy, 28 (19%) to TDF plus emctritabine, 14 (9%) patients to ETV monotherapy and 6 (4%) patients to other antivirals. Median duration of therapy after switch was 14 months. Reasons for the switch were following: 33 patients slow-response/non-response, 14 had drug-related renal impairment, 5 due to pregnancy, 2 after liver transplantation and 95 patients were switched for other reasons. Methods Number of patients achieved HBeAg seroconversion and complete virological response (CR) (HBV DNA<12 IU/ml) was compared (LAM+ADV vs. switch). Differences between serum levels of HBV DNA, creatinine and phosphate and estimated glomerular filtration rates (eGFR) were assessed at each time-point and compared between groups and with baseline. HBV genotypic resistance was tested in all patients with suboptimal response by direct sequencing. Results: Baseline HBV DNA was significantly higher in LAM+ADV vs switch group (median log10 4.6 vs 0.89 IU/ml, p<0.01), there was higher proportion of responses after switch than at time of switch and when compared to LAM+ADV (switch baseline 76% vs m3 switch 91%, p=0.02 vs m3 LAM+ADV 48%, p<0.01). On LAM+ADV therapy 14 patients achieved HBeAg and 3 patients HBsAg seroconversion and additional 3 patients and 1 patient seroconverted HBeAg and HBsAg after switch. No viral mutations associated with drug resistance were detected in LAM+ADV and after switch. There were no significant differences in serum creatinine or eGFR between groups at each time-point, but comparing to baseline there was significant decrease in eGFR from M18 onwards in LAM+ADV group (82.2 vs76.2 ml/s, p=0.04). The proportion of patients with eGFR <60 ml/s did not changed during LAM+ADV therapy and after switch. Serum phosphate levels [mmol/l] fell on therapy in LAM+ADV from M12 (M12: −0.04, M18: −0.06 and M24: −0.05) and remained unchanged after switch. Conclusion: Switch to other nucleos(t)ide analogues from long-term de-novo combination LAM+ADV therapy was efficient and was not associated with impact on renal/bone safety.